A case study on effectiveness and efficiency of billing the account receivable in Sarku Engineering, Underwater Services, SapuraCrest Petroleum / Syairazi Othman - Othman, Syairazi (2009)
SapuraCrest Petroleum Berhad is one of the largest vendors company in oil and gas industry in Malaysia. Its intercompany, Sarku Engineering Services Sdn Bhd (SES) is one of Malaysia’s first companies in this line of work that fully owned by locals, and among the first to have their own engineering – work vessel and workboats fitted to the highest standards in the industry. This exploration study was conducted out to study on the effectiveness and efficiency of billing towards Sarku Engineering Services Sdn Bhd (SES) of account receivables. This study is also to identify what are the issues and solutions for the effectiveness and efficiency of billing. In Sarku Engineering Services Sdn Bhd (SES), billing is important because it is company’s collection and its show company’s performance. Tools that used to collect information were from primary and secondary data such as my supervisor and internet.